Preparation method and application of catalyst for co-thermal cracking of waste plastic and biomass

By using a catalyst prepared from FCC waste catalyst and phosphorus-modified ZSM-5 molecular sieve, the problem of small pore size and insufficient activity of the co-thermal cracking catalyst was solved, and efficient co-thermal cracking of waste plastics and biomass was achieved, with a liquid yield greater than 70%. .

CN119327504AActive Publication Date: 2025-01-21PETROCHINA CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202310887693.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The prior art CCP thermal cracking catalyst has small pore size and insufficient activity, resulting in low liquid yield.

Method used

Using FCC waste catalyst as a carrier, combined with metal oxide and phosphorus-modified ZSM-5 molecular sieve as active components, a catalyst with larger pore size and pore volume is formed through ball milling and phosphorus modification.

Benefits of technology

The activity of the catalyst is improved, the co-pyrolysis conversion efficiency of waste plastics and biomass is promoted, and the liquid yield is greater than 70%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method and application of a catalyst for co-thermal cracking of waste plastics and biomass, and the preparation method comprises the following steps: step 1, uniformly mixing an FCC waste catalyst, sodium carbonate and a metal oxide precursor to form powder; step 2, carrying out phosphorus modification on the HZSM-5 molecular sieve; and step 3, mixing and pulping the mixture obtained in the step 1, the phosphorus-modified ZSM-5 molecular sieve obtained in the step 2, a binder and water to form microspheres, and roasting to obtain the catalyst for co-thermal cracking of waste plastics and biomass. The catalyst prepared by the method has larger pore diameter and pore volume and is used for co-thermal cracking of waste plastics and biomass, and the liquid yield is greater than 70%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a catalyst for co-pyrolysis of waste plastics and biomass, and application of the preparation method in the co-pyrolysis process of waste plastics and biomass. Background Art

[0002] As part of urban solid waste, waste plastics damage environmental hygiene and harm the ecosystem. Common treatment methods include landfill, incineration and recycling. Among them, landfill and incineration will cause secondary pollution. Therefore, devoting ourselves to the development of recycling and utilization of waste plastics is a green road to sustainable development.

[0003] In addition, most of today's energy and chemical raw materials come from fossil resources. Under the severe test of energy reserves and environmental problems, the development of renewable energy such as biomass energy has attracted the attention of many researchers.

[0004] Patent CN111876177A discloses that the biomass is dried and crushed and sieved, and the biomass with a particle size of ≤3nm is dried again; the waste plastic is ground and sieved, and the waste plastic with a particle size of <80 mesh is dried, and the treated biomass and waste plastic are mixed evenly at a mass ratio of 1:1-10 and placed in a reaction device for heating treatment to obtain bio-oil with a yield of 30%-70%. The liquid yield of this technology is less than 70%, and it needs to be heated in stages, and the procedure is relatively complicated.

[0005] Patent CN103920526B discloses a composite catalyst that uses HZSM-5 molecular sieve as a catalyst carrier, first loading non-metallic element phosphorus on the catalyst carrier, and then loading transition metal elements nickel, zinc or copper. The catalyst carrier of this technology is HZSM-5 molecular sieve, which has a small pore size and is not conducive to the diffusion of large molecules.

[0006] Patent CN107118793B treats HZSM-5 by alkali treatment to prepare multi-level pore HZSM-5, and then uses atomic layer deposition to deposit metal sources into the multi-level pore HZSM-5. The catalyst is used for co-cracking of biomass and oils, which can effectively slow down the deactivation due to carbon deposition and improve the yield of aromatics. However, although this technology treats HZSM-5 by alkali treatment to prepare multi-level pore HZSM-5, its pore size distribution peak is less than 1nm, and the mesopore diameter in the electron microscope photo is 2-3nm, and its pore size is still difficult to meet the requirements.

[0007] Patent CN103691429B discloses that the catalyst consists of two parts: a carrier and an active component, and the active component is loaded onto the carrier by an impregnation method. The carrier is a byproduct of rapid pyrolysis carbon from the process of rapid thermal cracking and liquefaction of biomass. After degreasing, deashing, activation, oxidation and other treatments are performed on the rapid pyrolysis carbon, it is formed into a mesopore and macropore channel structure mainly of 20-80nm, and the active component is a transition metal, which is impregnated onto the carrier through steps such as loading and reduction to prepare a catalyst for rapid thermal cracking and liquefaction of biomass. The preparation of the carrier of this technology requires degreasing, deashing, activation, oxidation and other treatments, the steps are complicated, and the thermal stability of the catalyst needs to be strengthened.

[0008] Therefore, there is still a need in the art to study catalysts for co-pyrolysis of waste plastics and biomass. Summary of the invention

[0009] The main purpose of the present invention is to provide a preparation method and application of a catalyst for co-pyrolysis of waste plastics and biomass, so as to overcome the defects of the co-pyrolysis catalyst in the prior art, such as small pore size and insufficient activity resulting in low yield of the catalytically obtained liquid.

[0010] In order to achieve the above object, the present invention provides a method for preparing a catalyst for co-pyrolysis of waste plastics and biomass, comprising the following steps:

[0011] Step 1, mixing FCC waste catalyst, sodium carbonate and metal oxide precursor uniformly to form powder;

[0012] Step 2, phosphorus-modifying the HZSM-5 molecular sieve;

[0013] Step 3, mixing and slurrying the mixture obtained in step 1, the phosphorus-modified ZSM-5 molecular sieve in step 2, a binder, and water to form microspheres, and calcining to obtain a catalyst for co-pyrolysis of waste plastics and biomass.

[0014] In the method for preparing a catalyst for co-pyrolysis of waste plastics and biomass described in the present invention, the metal in the metal oxide precursor is a Group IIA metal or a transition metal.

[0015] The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass of the present invention comprises the following steps: the metal oxide precursor is calculated as metal oxide, and the dry basis mass ratio of the sodium carbonate, the metal oxide precursor and the FCC waste catalyst is 0.01-0.05:0.05-0.2:1.

[0016] The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass of the present invention comprises the following steps: in step 1, the powder is formed by ball milling, and the ball milling time is 10-20 minutes.

[0017] The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass of the present invention, wherein in step 2, the method for phosphorus modification of HZSM-5 molecular sieve is: impregnating the HZSM-5 molecular sieve with a solution containing a phosphorus precursor, drying at 120-140° C. for 2-3 hours, and then calcining at 500-600° C. for 1-3 hours to obtain a phosphorus-modified ZSM-5 molecular sieve.

[0018] The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass of the present invention comprises the following steps: the phosphorus-containing precursor is at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium phosphate; phosphorus is calculated as P2O5, and the mass ratio of phosphorus to the dry basis of HZSM-5 molecular sieve is 1%-5%.

[0019] In the method for preparing a catalyst for co-pyrolysis of waste plastics and biomass of the present invention, the amount of the phosphorus-modified ZSM-5 molecular sieve added in step 3 is 5%-20% of the dry basis mass of the FCC waste catalyst.

[0020] The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass of the present invention, wherein the binder is selected from at least one of aluminum sol, neutral silica sol, and acidic silica sol; and the amount of the binder added in step 3 is 2%-10% of the dry basis mass of the FCC waste catalyst.

[0021] The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass of the present invention comprises the following steps: in step 1, the metal oxide precursor is selected from at least one of calcium carbonate, magnesium carbonate and zinc carbonate; in step 3, the calcination temperature is 830-900° C. and the calcination time is 1-3 hours.

[0022] In order to achieve the above purpose, the present invention also provides the use of the catalyst obtained by the above preparation method in the co-pyrolysis of waste plastics and biomass, characterized in that the mass ratio of waste plastics to biomass is 1:1-10:1; the conditions for co-pyrolysis are: pyrolysis temperature 400-550°C, pressure 0.1-1.0MPa, and the amount of catalyst added is 2wt%-15wt% of the total mass of waste plastics and biomass.

[0023] Beneficial effects of the present invention:

[0024] The present invention uses FCC waste catalyst as a carrier, metal oxides and phosphorus-modified ZSM-5 molecular sieves as active components. The original pore structure of the FCC waste catalyst and the punching effect of CO2 make the catalyst have a larger pore size and pore volume, thereby improving the accessibility of the active components and making the liquid yield greater than 70%.

[0025] The catalyst of the present invention adopts FCC waste catalyst, which not only solves the problem of treating FCC waste catalyst, but also realizes the reuse of FCC waste catalyst, and the process is simple and easy to industrialize. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is described in detail below. The following implementation modes are implemented on the premise of the technical scheme of the present invention, and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following implementation modes. The structures or experimental methods of specific conditions are not specified in the following implementation modes, and generally conventional conditions are followed.

[0027] The present invention provides a method for preparing a catalyst for co-pyrolysis of waste plastics and biomass, comprising the following steps:

[0028] Step 1, mixing FCC waste catalyst, sodium carbonate and metal oxide precursor uniformly to form powder;

[0029] Step 2, phosphorus-modifying the HZSM-5 molecular sieve;

[0030] Step 3, mixing and slurrying the mixture obtained in step 1, the phosphorus-modified ZSM-5 molecular sieve in step 2, a binder, and water to form microspheres, drying, and roasting to obtain a catalyst for co-pyrolysis of waste plastics and biomass.

[0031] At present, most of the FCC waste catalysts are generally disposed of by landfill. The regeneration processes of a few FCC waste catalysts mainly include acid washing, carbonylation-chlorination, sulfidation-oxidation and magnetic rotation to remove heavy metals and restore the activity of FCC waste catalysts. However, these methods have problems such as complicated processes and high regeneration costs.

[0032] The present invention uses FCC waste catalyst as a carrier, metal oxide and phosphorus-modified ZSM-5 molecular sieve as active components, and sodium carbonate is added during the catalyst preparation process. The catalyst has a CO2 punching effect during the calcination process. In this way, combined with the original pore structure of the FCC waste catalyst, the obtained catalyst has a larger pore size and pore volume, thereby improving the accessibility of the active components dispersed on the pore surface, promoting the co-thermal cracking conversion efficiency of waste plastics and biomass, and making the liquid yield obtained by the catalyst catalysis greater than 70%.

[0033] In addition, the ball milling of the FCC waste catalyst and sodium carbonate of the present invention can activate metals, promote the synergistic effect of different metal ions, and help increase the number of reactive activity, thereby further improving the cracking reaction efficiency of the obtained catalyst.

[0034] In detail, step 1 of the present invention is: mixing FCC waste catalyst, sodium carbonate and metal oxide precursor uniformly to form powder.

[0035] The present invention does not specifically limit the FCC waste catalyst, and any catalytic cracking catalyst discarded from the catalytic cracking process may be used. The present invention also does not specifically limit the structure and element content of the FCC waste catalyst.

[0036] In one embodiment, the metal in the metal oxide precursor of the present invention is a Group IIA metal or a transition metal, such as calcium, magnesium, zinc, etc., and the metal oxide precursor can be a metal carbonate, such as at least one of calcium carbonate, magnesium carbonate, and zinc carbonate.

[0037] The present invention does not particularly limit the method for forming the powder of the mixture of the FCC waste catalyst, sodium carbonate and metal oxide precursor. Preferably, the powder forming method is ball milling, more specifically mechanical ball milling, so that the metal on the FCC waste catalyst can be activated, the number of active centers of the obtained catalyst can be increased, and the resource utilization of the FCC waste catalyst can be realized. In one embodiment, the ball milling time is 10-20 minutes.

[0038] In one embodiment, the metal oxide precursor is calculated as metal oxide, and the mass ratio of the sodium carbonate of the present invention, the metal oxide precursor and the FCC waste catalyst on a dry basis is: 0.01-0.05: 0.05-0.2: 1. In another embodiment, the mass ratio of the metal oxide precursor of the present invention to the FCC waste catalyst on a dry basis is: 0.08: 1-0.15: 1.

[0039] Step 2 of the present invention is: modifying the HZSM-5 molecular sieve with phosphorus.

[0040] The present invention does not specifically limit the HZSM-5 molecular sieve, and it can be a commercially available HZSM-5 molecular sieve, or it can be prepared according to the prior art method. In one embodiment, the silicon-aluminum ratio of the HZSM-5 molecular sieve is 25-50.

[0041] In the present invention, the HZSM-5 molecular sieve is first phosphorus-modified before being prepared as a catalyst. In one embodiment, the phosphorus modification is performed by impregnation, such as impregnating the HZSM-5 molecular sieve in a solution containing a phosphorus precursor, and then drying and calcining to obtain a phosphorus-modified HZSM-5 molecular sieve.

[0042] Wherein, the phosphorus-containing precursor may be at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium phosphate. The solution of the phosphorus-containing precursor may be an aqueous solution of at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium phosphate. The impregnation method may be equal volume impregnation, excessive impregnation, etc. The impregnated ZSM-5 molecular sieve is dried and calcined, the drying temperature may be 120-140°C, the drying time may be 2-3 hours, the calcination temperature may be 500-600°C, and the calcination time may be 1-3 hours.

[0043] In one embodiment, in the phosphorus-modified ZSM-5 molecular sieve, phosphorus is calculated as P2O5, and the mass ratio of phosphorus to the dry basis of the ZSM-5 molecular sieve is 1%-5%.

[0044] Step 3 of the present invention is: mixing and slurrying the mixture obtained in step 1, the phosphorus-modified ZSM-5 molecular sieve in step 2, a binder and water to form microspheres, and calcining to obtain a catalyst for co-pyrolysis of waste plastics and biomass.

[0045] The binder of the present invention is a conventional binder in the art. In one embodiment, the binder of the present invention is selected from a mixture of one or more of aluminum sol, neutral silica sol, and acidic silica sol. The amount of the binder added is 2%-10% of the dry basis weight of the FCC waste catalyst.

[0046] In one embodiment, the amount of phosphorus-modified ZSM-5 molecular sieve added is 5% to 20% of the dry mass of the FCC spent catalyst.

[0047] The present invention does not particularly limit the amount of water added in step 3, as long as a slurry can be formed. The method of forming microspheres is, for example, spray drying. The calcination temperature in step 3 is, for example, 830-900° C., and the calcination time is, for example, 1-3 hours.

[0048] The catalyst prepared by the method of the present invention has a large pore size and pore volume, and is suitable as a catalyst for the co-thermal cracking of waste plastics and biomass. In one embodiment, the mass ratio of waste plastics to biomass of the present invention is 1:1-10:1. In another embodiment, the co-thermal cracking conditions are: cracking temperature 400-550°C, pressure 0.1-1.0MPa, and the amount of catalyst added is 2-15wt% of the sum of the mass of waste plastics and biomass.

[0049] The present invention does not particularly limit the sources of waste plastics and biomass. In one embodiment, the waste plastics are a mixture of one or more of waste low-density polyethylene (relative molecular weight of 0.910-0.925), high-density polyethylene (relative molecular weight of 0.941-0.965), polypropylene, and polystyrene, and the biomass is a mixture of one or more of sawdust, straw, and waste dregs.

[0050] The technical solution of the present invention will be described below through specific embodiments.

[0051] Source of raw materials or equipment:

[0052] FCC waste catalyst (specific surface area 113.7m 2 / g, pore volume is 0.127cm 3 / g), sodium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, phosphoric acid, diammonium hydrogen phosphate and ammonium phosphate were all analytically pure and produced by Sinopharm Group; alumina sol (Al2O3 19.4wt%), neutral silica sol (SiO2 30wt%), acidic silica sol (SiO2 30wt%), HZSM-5 (crystallinity 90%, silicon-aluminum ratio 30) were produced by Lanzhou Petrochemical Company.

[0053] Evaluation and analysis methods:

[0054] The pore volume and pore size of the catalyst were determined by low-temperature nitrogen adsorption-desorption method (for the analysis method, see "Petrochemical Analysis Method (RIPP Experimental Method)", edited by Yang Cuiding et al., Science Press, published in 1990), and the catalyst reaction performance was evaluated using a small fixed bed.

[0055] Example 1

[0056] 1021 g of dry FCC waste catalyst, 21 g of sodium carbonate and 306 g of calcium carbonate were mixed evenly and mechanically ball-milled for 12 minutes; 200 g of HZSM-5 molecular sieve was impregnated with a solution containing 7.6 g of diammonium hydrogen phosphate, dried at 130°C for 3 hours, and calcined at 570°C for 1.5 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 101 g of dry phosphorus-modified ZSM-5 molecular sieve, 82 g of aluminum sol and 3403 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 870°C for 1.5 hours to obtain catalyst C-1 for thermal cracking of waste plastics, which had an average pore size of 9.2 nm and a total pore volume of 0.59 cm 3 / g.

[0057] Using waste plastics and biomass as raw materials (polypropylene, straw mass percentage: 80%, 20%), co-thermal cracking was carried out at a temperature of 450°C, a pressure of 0.7 MPa, and a catalyst: (waste plastics and biomass) = 5wt% reaction conditions, with a liquid yield of 79.7%.

[0058] Example 2

[0059] 1434 g of dry FCC waste catalyst, 43 g of sodium carbonate and 243 g of magnesium carbonate were mixed evenly and mechanically ball-milled for 15 minutes; 330 g of HZSM-5 molecular sieve was impregnated with a solution containing 13.6 g of phosphoric acid, dried at 139° C. for 2 hours, and calcined at 530° C. for 2.5 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 215 g of dry phosphorus-modified ZSM-5 molecular sieve, 72 g of acidic silica sol and 4780 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 835° C. for 2.5 hours to obtain the catalyst C-2 for co-thermal cracking of waste plastics and biomass, which has an average pore diameter of 8.7 nm and a total pore volume of 0.60 cm 3 / g.

[0060] Using waste plastics and biomass as raw materials (polystyrene, wood chips mass percentage: 90%, 10%), co-thermal cracking was carried out under the reaction conditions of temperature 410°C, pressure 0.3Mpa, catalyst: (waste plastics and biomass) = 5.7wt%, and the liquid yield was 83.5%.

[0061] Example 3

[0062] 1507 g of dry FCC waste catalyst, 16 g of sodium carbonate and 302 g of zinc carbonate were mixed evenly and mechanically ball-milled for 19 minutes; 350 g of HZSM-5 molecular sieve was impregnated with a solution containing 7.4 g of ammonium phosphate, dried at 130°C for 2.2 hours, and calcined at 510°C for 2.8 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 121 g of dry phosphorus-modified ZSM-5 molecular sieve, 106 g of neutral silica sol and 5023 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 895°C for 1.1 hours to obtain the catalyst C-3 for co-thermal cracking of waste plastics and biomass, which has an average pore size of 9.3 nm and a total pore volume of 0.65 cm 3 / g.

[0063] Using waste plastics and biomass as raw materials (low-density polyethylene, high-density polyethylene, straw mass percentage: 30%, 30%, 40%), co-thermal cracking was carried out under the reaction conditions of temperature 465°C, pressure 0.6Mpa, catalyst: (waste plastics and biomass) = 9wt%, and the liquid yield was 77.3%.

[0064] Example 4

[0065] 1556 g of dry FCC waste catalyst, 78 g of sodium carbonate, 125 g of zinc carbonate and 125 g of calcium carbonate were mixed evenly and mechanically ball-milled for 11 minutes; 150 g of HZSM-5 molecular sieve was impregnated with a solution containing 14 g of diammonium hydrogen phosphate, dried at 133° C. for 2.6 hours, and calcined at 570° C. for 2.3 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 94 g of dry phosphorus-modified ZSM-5 molecular sieve, 31 g of neutral silica sol, 47 g of acidic silica sol and 5932 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 850° C. for 2 hours to obtain the catalyst C-4 for co-thermal cracking of waste plastics and biomass, which has an average pore diameter of 9.2 nm and a total pore volume of 0.63 cm 3 / g.

[0066] Using waste plastics and biomass as raw materials (polypropylene, high-density polyethylene, straw, and waste residue in mass percentages of 20%, 40%, 20%, and 20%), co-thermal cracking was carried out at a temperature of 525°C, a pressure of 0.9 MPa, and a catalyst of (waste plastics and biomass) = 9wt%, with a liquid yield of 75.1%.

[0067] Example 5

[0068] 1197 g of dry FCC waste catalyst, 48 g of sodium carbonate, 239 g of magnesium carbonate and 132 g of calcium carbonate were mixed evenly and mechanically ball-milled for 15 minutes; 300 g of HZSM-5 molecular sieve was impregnated with a solution containing 25 g of ammonium phosphate, dried at 127° C. for 2.9 hours, and calcined at 540° C. for 2 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 239 g of dry phosphorus-modified ZSM-5 molecular sieve, 36 g of aluminum sol, 48 g of acidic silica sol and 3721 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 880° C. for 1 hour to obtain the catalyst C-5 for co-thermal cracking of waste plastics and biomass, which has an average pore diameter of 8.1 nm and a total pore volume of 0.59 cm 3 / g.

[0069] Using waste plastics and biomass as raw materials (polypropylene, high-density polyethylene, polystyrene, wood chips, straw, and waste dregs in mass percentages of 20%, 30%, 20%, 10%, 10%, and 10%), co-thermal cracking was carried out under the reaction conditions of temperature 495°C, pressure 0.5 MPa, and catalyst: (waste plastics and biomass) = 4.5wt%, with a liquid yield of 77.4%.

[0070] Example 6

[0071] 1867 g of dry FCC waste catalyst, 55 g of sodium carbonate, 260 g of magnesium carbonate and 112 g of zinc carbonate were mixed evenly and mechanically ball-milled for 10 minutes; 380 g of HZSM-5 molecular sieve was impregnated with a solution containing 21 g of diammonium hydrogen phosphate, dried at 131° C. for 2.4 hours, and then calcined at 590° C. for 1.8 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 243 g of dry phosphorus-modified ZSM-5 molecular sieve, 19 g of aluminum sol, 37 g of neutral silica sol and 6216 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 840° C. for 2.4 hours to obtain the catalyst C-6 for co-thermal cracking of waste plastics and biomass, which has an average pore diameter of 9.3 nm and a total pore volume of 0.69 cm 3 / g.

[0072] Using waste plastics and biomass as raw materials (polypropylene, low-density polyethylene, high-density polyethylene, polystyrene, wood chips, straw, and waste dregs in mass percentages of 20%, 15%, 20%, 20%, 5%, 10%, and 10%), co-thermal cracking was carried out under the reaction conditions of temperature 470°C, pressure 0.3Mpa, and catalyst: (waste plastics and biomass) = 5.5wt%, with a liquid yield of 79.3%.

[0073] Example 7

[0074] 1587g of dry FCC waste catalyst, 78g of sodium carbonate, 126g of calcium carbonate, 64g of magnesium carbonate and 95g of zinc carbonate were mixed evenly and mechanically ball-milled for 16 minutes; 410g of HZSM-5 molecular sieve was impregnated with a solution containing 38g of diammonium hydrogen phosphate, dried at 137°C for 2.3 hours, and calcined at 530°C for 2.6 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 285g of dry phosphorus-modified ZSM-5 molecular sieve, 47g of aluminum sol and 7568g of deionized water, spray-dried to form microspheres, and calcined at 860°C for 2.2 hours to obtain the catalyst C-7 for co-thermal cracking of waste plastics and biomass, which has an average pore diameter of 9.7nm and a total pore volume of 0.67cm 3 / g.

[0075] Using waste plastics and biomass as raw materials (low-density polyethylene, high-density polyethylene, polystyrene, straw, and waste residue by mass percentage: 30%, 5%, 30%, 20%, and 15%), co-thermal cracking was carried out under the reaction conditions of temperature 540°C, pressure 0.2 MPa, and catalyst: (waste plastics and biomass) was 6wt%, and the liquid yield was 76.8%.

[0076] Example 8

[0077] 1289 g of dry FCC waste catalyst, 49 g of sodium carbonate and 384 g of magnesium carbonate were mixed evenly and mechanically ball-milled for 18 minutes; 220 g of HZSM-5 molecular sieve was impregnated with a solution containing 16 g of diammonium hydrogen phosphate, dried at 137° C. for 2.3 hours, and then calcined at 555° C. for 2.5 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 116 g of dry phosphorus-modified ZSM-5 molecular sieve, 25 g of aluminum sol, 38 g of neutral silica sol, 51 g of acidic silica sol and 7027 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 850° C. for 2 hours to obtain the catalyst C-8 for co-thermal cracking of waste plastics and biomass, which has an average pore diameter of 8.7 nm and a total pore volume of 0.59 cm 3 / g.

[0078] Using waste plastics and biomass as raw materials (mass percentage of low-density polyethylene, high-density polyethylene, straw, and wood chips: 30%, 20%, 30%, and 20%), co-thermal cracking was carried out under the reaction conditions of temperature 440°C, pressure 0.8 MPa, and catalyst: (waste plastics and biomass) = 8wt%, and the liquid yield was 72.1%.

[0079] Example 9

[0080] 1397 g of dry FCC waste catalyst, 28 g of sodium carbonate and 195 g of calcium carbonate were mixed evenly and mechanically ball-milled for 15 minutes; 270 g of HZSM-5 molecular sieve was impregnated with a solution containing 8 g of phosphoric acid, dried at 126° C. for 2.7 hours, and calcined at 535° C. for 2.9 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 153 g of dry phosphorus-modified ZSM-5 molecular sieve, 73 g of acidic silica sol and 4642 g of deionized water, spray-dried to form microspheres, and calcined at 870° C. for 1.5 hours to obtain the catalyst C-9 for co-thermal cracking of waste plastics and biomass, which has an average pore size of 9.1 nm and a total pore volume of 0.66 cm 3 / g.

[0081] Using waste plastics and biomass as raw materials (low-density polyethylene, waste residue mass percentage: 60%, 40%), co-thermal cracking was carried out at a temperature of 525°C, a pressure of 0.5 MPa, and a catalyst: (waste plastics and biomass) = 7wt% reaction conditions, with a liquid yield of 75.1%.

[0082] Comparative Example 1

[0083] 1021 g of dry FCC waste catalyst and 21 g of sodium carbonate were mixed evenly and mechanically ball-milled for 12 minutes; 200 g of HZSM-5 molecular sieve was impregnated with a solution containing 7.6 g of diammonium hydrogen phosphate, dried at 130° C. for 3 hours, and calcined at 570° C. for 1.5 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 101 g of dry phosphorus-modified ZSM-5 molecular sieve, 82 g of aluminum sol, and 3403 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 870° C. for 1.5 hours to obtain the catalyst D-1 for thermal cracking of waste plastics, which had an average pore size of 7.6 nm and a total pore volume of 0.47 cm 3 / g.

[0084] Using waste plastics and biomass as raw materials (polypropylene and straw mass percentage: 80%, 20%), co-thermal cracking was carried out at a temperature of 450°C, a pressure of 0.7 MPa, and a catalyst: (waste plastics and biomass) = 5wt% reaction conditions, with a liquid yield of 62.7%.

[0085] Comparative Example 2

[0086] 1507 g of dry FCC waste catalyst and 302 g of zinc carbonate were mixed evenly and mechanically ball-milled for 19 minutes; 350 g of HZSM-5 molecular sieve was impregnated with a solution containing 7.4 g of ammonium phosphate, dried at 130°C for 2.2 hours, and calcined at 510°C for 2.8 hours to obtain phosphorus-modified ZSM-5 molecular sieve; the ball-milled product was mixed with 121 g of dry phosphorus-modified ZSM-5 molecular sieve, 106 g of neutral silica sol, and 5023 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 895°C for 1.1 hours to obtain the catalyst D-2 for co-thermal cracking of waste plastics and biomass, which has an average pore size of 8.1 nm and a total pore volume of 0.55 cm 3 / g.

[0087] Using waste plastics and biomass as raw materials (low-density polyethylene, high-density polyethylene, straw mass percentage: 30%, 30%, 40%), co-thermal cracking was carried out under the reaction conditions of temperature 465°C, pressure 0.6Mpa, catalyst: (waste plastics and biomass) = 9wt%, and the liquid yield was 67.8%.

[0088] Comparative Example 3

[0089] 536 g of dry FCC waste catalyst was calcined at 870°C for 1.5 hours to obtain the waste plastic thermal cracking catalyst D-3, which had an average pore diameter of 6.1 nm and a total pore volume of 0.13 cm 3 / g. Waste plastics and biomass were used as raw materials (polypropylene, high-density polyethylene, straw, waste dregs by mass percentage: 20%, 40%, 20%, 20%), and co-pyrolysis was carried out at a temperature of 525°C, a pressure of 0.9 MPa, and a catalyst: (waste plastics and biomass) = 9wt% reaction conditions, with a liquid yield of 47.2%.

[0090] Comparative Example 4

[0091] 1867 g of dry FCC waste catalyst, 55 g of sodium carbonate, 260 g of magnesium carbonate and 112 g of zinc carbonate were mixed evenly, mechanically ball-milled for 10 minutes, mixed with 19 g of aluminum sol, 37 g of neutral silica sol and 6216 g of deionized water for slurrying, spray-dried to form microspheres, and calcined at 840° C. for 2.4 hours to obtain the catalyst D-4 for co-pyrolysis of waste plastics and biomass, which has an average pore diameter of 9.7 nm and a total pore volume of 0.63 cm 3 / g.

[0092] Using waste plastics and biomass as raw materials (polypropylene, low-density polyethylene, high-density polyethylene, polystyrene, wood chips, straw, and waste dregs in mass percentages of 20%, 15%, 20%, 20%, 5%, 10%, and 10%), co-thermal cracking was carried out under the reaction conditions of temperature 470°C, pressure 0.3Mpa, and catalyst: (waste plastics and biomass) = 5.5wt%, with a liquid yield of 67.9%.

[0093] Comparative Example 5

[0094] 1587 g of dry FCC waste catalyst, 78 g of sodium carbonate, 296 g of calcium carbonate, 234 g of magnesium carbonate and 165 g of zinc carbonate were mixed evenly, mechanically ball-milled for 16 minutes, mixed with 47 g of aluminum sol and 7568 g of deionized water, spray-dried to form microspheres, and calcined at 860° C. for 2.2 hours to obtain the catalyst D-5 for co-pyrolysis of waste plastics and biomass, which has an average pore diameter of 11.3 nm and a total pore volume of 0.71 cm 3 / g.

[0095] Using waste plastics and biomass as raw materials (low-density polyethylene, high-density polyethylene, polystyrene, straw, and waste residue by mass percentage: 30%, 5%, 30%, 20%, and 15%), co-thermal cracking was carried out under the reaction conditions of temperature 540°C, pressure 0.2 MPa, and catalyst: (waste plastics and biomass) 6wt%, and the liquid yield was 68.1%.

[0096] As shown in the above examples and comparative examples, the catalyst prepared by the method of the present invention has a larger pore size and pore volume, and uses metal oxides and phosphorus-modified ZSM-5 molecular sieves as active components, and is used to catalyze the co-thermal cracking of waste plastics and biomass, with a higher liquid yield.

[0097] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a catalyst for co-pyrolysis of waste plastics and biomass, characterized in that: The steps include: Step 1, mixing FCC waste catalyst, sodium carbonate and metal oxide precursor uniformly to form powder; Step 2, phosphorus-modifying the HZSM-5 molecular sieve; Step 3, mixing and slurrying the mixture obtained in step 1, the phosphorus-modified ZSM-5 molecular sieve in step 2, a binder, and water to form microspheres, and calcining to obtain a catalyst for co-pyrolysis of waste plastics and biomass.

2. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 1, characterized in that: The metal in the metal oxide precursor is a Group IIA metal or a transition metal.

3. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 1, characterized in that: The metal oxide precursor is calculated as metal oxide, and the mass ratio of the sodium carbonate, the metal oxide precursor and the FCC waste catalyst on a dry basis is: 0.01-0.05:0.05-0.2:

1.

4. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 1, characterized in that: In step 1, the powder is formed by ball milling, and the ball milling time is 10-20 minutes.

5. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 1, characterized in that: In step 2, the method for phosphorus modification of HZSM-5 molecular sieve is: impregnating HZSM-5 molecular sieve with a solution containing a phosphorus precursor, drying at 120-140° C. for 2-3 hours, and calcining at 500-600° C. for 1-3 hours to obtain a phosphorus-modified ZSM-5 molecular sieve.

6. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 5, characterized in that: The phosphorus-containing precursor is at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium phosphate; the phosphorus is calculated as P2O5, and the mass ratio of phosphorus to the dry basis of the HZSM-5 molecular sieve is 1%-5%.

7. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 1, characterized in that: In step 3, the amount of the phosphorus-modified ZSM-5 molecular sieve added is 5%-20% of the dry basis mass of the FCC waste catalyst.

8. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 1, characterized in that: The binder is selected from at least one of aluminum sol, neutral silica sol and acidic silica sol; the amount of the binder added in step 3 is 2%-10% of the dry basis weight of the FCC waste catalyst.

9. The method for preparing a catalyst for co-pyrolysis of waste plastics and biomass according to claim 1, characterized in that: In step 1, the metal oxide precursor is selected from at least one of calcium carbonate, magnesium carbonate and zinc carbonate; in step 3, the calcination temperature is 830-900° C. and the calcination time is 1-3 hours.

10. Use of the catalyst obtained by the preparation method according to any one of claims 1 to 9 in the co-pyrolysis of waste plastics and biomass, characterized in that: The mass ratio of waste plastics to biomass is 1:1-10:1; the conditions for co-thermal cracking are: cracking temperature 400-550°C, pressure 0.1-1.0MPa, and the amount of catalyst added is 2wt%-15wt% of the total mass of waste plastics and biomass.

Citation Information

Patent Citations

  • Catalyst for rapid pyrolysis and liquefaction of biomass as well as preparation method and application thereof

    CN103691429B

  • Composite catalyst for preparing aromatics by catalytic pyrolysis and preparation method thereof

    CN103920526B

  • Application of a metal-supported catalyst in the co-cracking of oil and biomass to prepare aromatics

    CN107118793B

  • Method for preparing biofuel by co-pyrolysis of biomass and waste plastics

    CN111876177A

  • Conversion of plastics to olefin and aromatic products with product recycle

    CN105121605A